Persepsi Perilaku Caring oleh Perawat Berhubungan dengan Stres Kerja - Roisul Umam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to analyze the relationship between nurses' job stress and perceptions of caring behavior. The method in this study used a correlation analytic research design with a cross-sectional approach. The analysis results using the Spearman correlation test obtained the calculated r-value of 0.876 and a significance value of Sig. (2-tailed) of 0.001 (<0.05). In conclusion, nurses' work stress has a significant relationship with the perception of caring behavior at RSI Sakinah Mojokerto. Keywords: Nurse, Perceptions of Caring Behavior, Stress